Comparative evaluation of glass ionomer cements in ART restorations: a 4-year non-randomized clinical trial - Tapety, Celiane Mary Carneiro; Paiva, Antonio Kleber Aragão; Albuquerque, Lívia Mont’Alverne de Barros; Dias, Déborah Vasconcelos Taumaturgo; Casselli, Denise Sá Maia; Rêgo, Rodrigo Otávio Citó César; Neves, Beatriz Gonçalves; Moreira, Mário Áureo Gomes (Brazilian Dental Science, 2025)
Objective: This study aimed to evaluate and compare the clinical performance of Class I occlusal Atraumatic Restorative Treatment (ART) restorations in permanent molars using two different glass ionomer cements, Ketac Molar Easy Mix (3M ESPE) and Vitro Molar (DFL), over a 4-year follow-up period. Material and Methods: A total of 56 ART restorations were performed in 34 children and adolescents aged 10 to 15 years from two public schools in Sobral, Ceará, Brazil. The selected cavities were assigned to the Ketac Molar Easy Mix group (KM) or the Vitro Molar group (VM), with 27 and 29 restorations, respectively. Evaluations were conducted based on the ART and the United States Public Health Service (USPHS) criteria at 6, 12, and 48 months. Statistical analyses were performed using McNemar and Chi-square tests, and the survival of the restorations was assessed using Kaplan-Meier survival analysis along with the log-rank test. Results: No statistically significant differences were observed in the clinical performance of ART restorations, whether comparing between groups or across the follow-up periods. The success rate at 4 years was 80% for the KM group and 76% for the VM group. Additionally, there was no significant difference between the survival curves of the groups studied (p > 0.05). Conclusion: After 4 years of follow-up, ART restorations in Class I cavities of permanent molars, performed with Ketac Molar Easy Mix and Vitro Molar, showed similar success rates, indicating good clinical performance. KEYWORDS Dental caries; Dental atraumatic restorative treatment; Dental restoration; Dentition, permanent; Glass ionomer cements.